DNA profiles from matchsticks. (29th July 2019) - Martin, Belinda; Blackie, Renee; Linacre, Adrian
ABSTRACT: Matchsticks may be found in forensic investigations, and here we report on a method to generate informative DNA profiles from a matchstick. Matchsticks were struck or held emulating striking, cellular material was removed using a tape-lift method and DNA profiles were generated from a small portion of the tape-lift using either direct PCR amplification or post-extraction PCR. Performing an extraction from the tape-lift prior to PCR resulted in 62% of profiles being informative, compared with 86% held and 97% struck matchsticks that underwent direct PCR. Incorporation of a tape-lift method into matchstick analysis allows effective collection of cellular material for the generation of genetic information from the striker of the matchstick.